Nation, Citizenship, and Belonging: Muslim Cultural Politics in Canada (American Journal of Islam and Society, 2009)
TheAssociation ofMuslim Social Scientists of NorthAmerica (AMSS) heldits fifth annual Canadian Regional Conference in Waterloo, Ontario, atWilfred Laurier University (WLU) on 21 May 2009. The Muslim StudiesOption Program Committee and the Department of Religion and Culture atWLU cosponsored this event, and Jasmin Zine (WLU) andMeena Sharify-Funk (WLU) were the cochairs. The Tessellate Institute, a CanadianMuslimthink tank, coordinated and cosponsored the keynote panel.The theme, “Nation, Citizenship, and Belonging: Muslim CulturalPolitics in Canada,” brought together academics, emerging scholars, andcommunity activists to explore critical questions about the space in the middlewhere engaged Muslim Canadians stand. In her opening remarks,Sharify-Funk identified that space as being located on an isthmus betweenthe realities of abject discrimination and the potentialities of citizenship. Sheremarked that this conference sought to ask the difficult questions aboutwhetherMuslim Canadians can engage the challenges and move beyond theinternal contradictions that inherently shape Muslim cultural politics ...